PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS EDMODO TERHADAP HASIL BELAJAR MAHASISWA - Susilawati, Evi (EDUTECH, 2018)
Abstract. The aim of this study was to see the learning outcomes of Civic Education subjects by using the Blended Learning model that based on Edmodo at the Faculty of Education of the Islamic University of North Sumatra. The population in this study amounted to 156 students and a sample of 59 students in the school year 2017/2018. The sample was taken using cluster random sampling technique and selected a total of 32 students from the History Education study program and 27 students of the Pancasila and Civic Education study program. Hypothesis testing is done by using one-way analysis of variance (Anava) at a 0.05 level of significance using the SPSS 24.0 for Windows program. Test the hypothesis in this study using an independent T test. Based on the T test results obtained a significance value of 0.032 with a significant value of 0.032 0.05 which rejects H0 and accepts H1. Based on the hypothesis test, it can be concluded that there are differences in learning outcomes of Citizenship Education courses for History Education students and students of the Pancasila and Civic Education Study program.Â Abstrak. Tujuan penelitian ini untuk melihat hasil belajar Mata Kuliah Pendidikan Kewarganegaraan (PKn) dengan menggunakan model pembelajaran blended Learning berbasis Edmodo di Fakultas Kependidikan dan Ilmu Pendidikan (FKIP) Universitas Islam Sumatera Utara. Populasi dalam penelitian ini berjumlah 156 mahasiswa dan sampelnya berjumlah 59 mahasiswa pada tahun pelajaran 2017/2018. Sampel diambil dengan menggunakan teknik cluster random sampling dan terpilih program studi Pendidkan Sejarah berjumlah 32 mahasiswa dan program studi Pendidikan Pancasila dan Kewarganegaraan berjumlah 27 mahasiswa. Uji hipotesis dilakukan dengan menggunakan analisis varians (Anava) one way pada taraf signifikansi 0.05 dengan menggunakan program SPSS 24.0 for Windows. Uji hipotesis pada penelitian ini menggunakan uji T independen. Berdasarkan hasil uji T diperoleh nilai signifikansi 0,032 dan dengan nilai signifikansi 0,0320,05 yang menolak H0 dan menerima H1. Berdasarkan uji hipotesis tersebut dapat disimpulkan bahwa terdapat perbedaan hasil belajar matakuliah PKn pada mahasiswa program studi Pendidikan Sejarah dan mahasiswa program studi Pendidikan Pancasila dan Kewarganegaraan.